Pengaruh Kinerja Keuangan Terhadap Return Saham (Studi Empiris Pada Sektor Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia Periode 2014-2016) - Sofi’yah Sofi’yah; Budi Wahono; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTReturn of shares is the profit gained from the ownership of the investor's share of theinvestment. In this study will be discussed about how the influence of financial ratios on theperformance of companies that affect stock returns